Identification and characterization of an Arabidopsis phosphate starvation-induced secreted acid phosphatase as a vegetative storage protein - Sun, Lichao (Plant science : an international journal of experimental plant biology, 2018)
Copyright © 2018 Elsevier B.V. All rights reserved.